Використання моделi комiркової рiдини для опису фазового переходу в простих рiдких лужних металах - Kozlovskii, M. P.; Dobush, O. A.; Pylyuk, I. V. (Publishing house "Academperiodika", 2018)
This article embraces a theoretical description of the first-order phase transition in liquid metals with the application of a cell fluid model. The results are obtained through the calculation of the grand partition function without a usage of phenomenological parameters. The Morse potential is used for the calculation of the equation of state and the coexistence curve. Specific results for sodium and potassium are obtained. Comparison of the outcome of analytic expressions with data of computer simulations is presented.